2008
DOI: 10.1080/10826080701202866
|View full text |Cite
|
Sign up to set email alerts
|

Social Normative Perceptions of Alcohol Use and Episodic Heavy Drinking Among Central and Eastern European Adolescents

Abstract: This study examined alcohol use and related social normative perceptions among a sample of 1,886 Central-Eastern European high school students. The youth represented in the study averaged 16.5 years of age and were from several localities in the countries of Hungary, Slovakia, Czech Republic, and Romania. Data for the study were collected through a school-based alcohol use survey that was completed in June 2005. Our results support the hypothesis that drinking was related to perception of the prevalence of alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 23 publications
6
28
0
3
Order By: Relevance
“…This finding is consistent with findings of previous research into perceptions of peer alcohol use in younger, school-aged adolescents in Central and Eastern Europe (Page et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is consistent with findings of previous research into perceptions of peer alcohol use in younger, school-aged adolescents in Central and Eastern Europe (Page et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
“…Research originating from the United States (Perkins, 2003), and replicated in some European studies (Lintonen & Konu, 2004;McAlaney et al, 2011;Page et al, 2008), suggests that individuals often appear to overestimate the frequency and amount of substance use of their peers. This is referred to in the literature as an overestimation or misperception of the descriptive norm and has been identified by surveying students on their own behavior or attitude and then asking them to indicate what they think the norm is for the majority of their peers at their institution.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the vast majority of social norms research has occurred within the USA and particularly the American college system, with similar work also being conducted in Canada (Perkins 2007b;Schmidt et al 2009 (Bewick et al 2008), Hungary, Slovakia, Romania and the Czech Republic (Page et al 2008). Several studies have found further evidence for misperceptions in Australian school children (Hughes et al 2008a) and Finnish adolescents (Lintonen and Konu 2004).…”
Section: Social Norms Research Outside Of the Usamentioning
confidence: 99%
“…У питању су погрешне пер-цепције пијења вршњака које се углавном састоје од ставова -да сви њихови вршњаци пију и да пију велике количине алкохола што утиче на пијење самих ис-питаника. Управо би програми превенције требало да обухвате тачне информа-ције о пијењу других и промену ставова о обрасцима пијења вршњака (Page, Ihasz, Hantiu, Simonek, Klarova, 2008). Ретроспективном студијом у којој је испи-тивана употреба алкохола код жена у Чешкој, у Прагу, на узорку од 608 (старо-сти 20-49) 6 пре и после друштвених и политичких промена дошло се до подата-ка да се употреба алкохола повећала од 3,6 на 4,8 литара у петогодишњем пери-оду, али је забрињавајући податак да је број жена које су имале епизоде тешког опијања повећао од 7,2 на 14%.…”
Section: конзумирање алкохола у чешкојunclassified